Pengaruh Pengendalian Internal, Asimetri Informasi, dan Ketaatan Aturan Akuntansi dengan Moralitas Individu sebagai Variabel Moderasi terhadap Kecenderungan Kecurangan Akuntansi - Fenty Astrina; Aprianto; Nurul Hutami Ningsih; Anggrelia Afrida; Desi Ratna Sari (Universitas Muhammadiyah Palembang, 2026)
This study aims to examine the factors influencing the tendency of accounting fraud by focusing on internal control, information asymmetry, and compliance with accounting rules, while also evaluating the moderating role of individual morality. The study employs a quantitative approach using Moderated Regression Analysis (MRA) based on data collected from public sector organizations.The results indicate that all main variables have a significant effect on the tendency of accounting fraud. Internal control and compliance with accounting rules are proven to reduce the likelihood of fraud, whereas information asymmetry increases the risk of fraudulent behavior. Furthermore, individual morality strengthens the effect of internal control and compliance with accounting rules but does not function effectively in moderating the relationship between information asymmetry and fraud tendency.These findings suggest that the tendency of accounting fraud is not only influenced by formal systems but also by individual characteristics. Therefore, effective fraud prevention strategies should integrate both structural and behavioral approaches simultaneously.